Komunitas Plankton pada saat Pasang dan Surut di Perairan Muara Sungai Demaan Kabupaten Jepara - Purwanti, Sri; Hariyati, Riche; Wiryani, Erry (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
This research was conductedÂ to study the plankton community at high tide and low tide of Demaan estuary, Jepara regency and to know the dynamics of abundance. The time of the research was done from April-June 2011. Sampling sites was determined by dividing the 3 stations in the estuary with Stratified Sampling Method, and two stations located on the river (station 4) and sea (station 5). The data determined are abundance index (N), diversity index (H '), evenness index (e), dominance index (C) and similarity index (IS). Physico-chemical factors were measured included water temperature, pH, salinity, DO, depth, turbidity, light penetration, and flow velocity. The plankton was found at high tide and low tide in April was Coelastrum sp. (Chlorophyta). Chaetoceros sp. (Chrysophyta) was found at high tide in May, whereas at low tide was Chlorella sp. (Chlorophyta). In June at high tide, there were found Chaetoceros sp. (Chrysophyta) and Arcella sp. (Protozoa), whereas at low tide were Bacteriastrum sp. (Chrysophyta), and Arcella sp. (Protozoa). The number of species at high tide was higher than at low tide, and the highest number of species present in June. Abundance index ofÂ plankton in the estuary at high tide ranged from 6300-18572 ind/L, whereas at low tide ranged from 3807-17848 ind/L. Diversity index (H ') at high tide ranged from 1,74 to 2,83, whereas at low tide ranged from 1,39 to 3,16. Evenness index (e) at high tide ranged from 0,6 to 0,85, whereas at low tide ranged from 0,63 to 0,86. Dominance index (C) at high tide ranged from 0,08 to 0,33, whereas at low tide ranged from 0,06 to 0,34. Similarity index at station of estuary average are not similar, except at station 1 at high tide and station 2 at low tide in June.Keyword : estuary, high tide and low tide, plankton